1986
DOI: 10.2307/1444931
|View full text |Cite
|
Sign up to set email alerts
|

Fishes of the North-Eastern Atlantic and the Mediterranean. Vol. 1

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 142.58.129.109 on Fri, 01 Jan 2016 01:30:03 UTC All use subject to JSTOR Terms and Conditions COPEIA, 1986, NO. 1 COPEIA, 1986, NO. 1 bat. A multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(98 citation statements)
references
References 0 publications
3
91
0
4
Order By: Relevance
“…Apart from the holotype of N. helgae (Holt and Byrne, 1908) from off the Irish coast, the other record of the species described was caught north of Madeira. Although it was first described as Crassispinus granulosus Maul (1948) and later as Neocyttus rhomboidalis, Alburquerque (1954Alburquerque ( -1956), reported differences between the sample from Madeira and other N. rhomboidalis samples described by other authors and suggested a revision of the specimen, that finally was identified as N. helgae by Wheeler (1973). Both records are the only ones listed in the review of the family Oreosomatidae in the Northeast Atlantic (Karrer, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the holotype of N. helgae (Holt and Byrne, 1908) from off the Irish coast, the other record of the species described was caught north of Madeira. Although it was first described as Crassispinus granulosus Maul (1948) and later as Neocyttus rhomboidalis, Alburquerque (1954Alburquerque ( -1956), reported differences between the sample from Madeira and other N. rhomboidalis samples described by other authors and suggested a revision of the specimen, that finally was identified as N. helgae by Wheeler (1973). Both records are the only ones listed in the review of the family Oreosomatidae in the Northeast Atlantic (Karrer, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Although the type of C. granulosus (MMF21668) was unavailable for loan, Manuel Biscoito (Museu Municipal do Funchal) kindly provided the authors with a colour transparency and radiograph. Examination of these were sufficient to confirm Wheeler's (1973) decision. Gilchrist, 1906 ( Fig.…”
Section: Comparisonsmentioning
confidence: 95%
“…It mostly agrees with the original description apart from the presence of teeth on the vomer ("vomer toothless" in Holt & Byrne 1908). Wheeler (1973) synonymised Crassispinus granulosus with N. helgae. Although the type of C. granulosus (MMF21668) was unavailable for loan, Manuel Biscoito (Museu Municipal do Funchal) kindly provided the authors with a colour transparency and radiograph.…”
Section: Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliography WHEELER (1973) gives a list of synonyms and references to the most important papers on morphology, ecology and distribution of the mediterranean Tripterygiidae. Table 1 adds all references to the biology of eastern-atlantic and mediterranean tripterygiids known to me and not given by WHEELER.…”
Section: Presentationmentioning
confidence: 99%